PROSPECTS AND IMPEDIMENTS OF FISH PROCESSING PLANTS IN NORTH EAST REGION OF BANGLADESH - Hossain, M M Hossain; Rahman, M A; Bapary, M A J; Bhattacharjee, D; Roy, N C; Rahman; H M M (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The present study was conducted during January 2015 to October 2015 to find out the prospects and impediments of Fish Processing Plants in North east region (Sylhet region). The study was performed by questionnaire- based data collection, the findings of the individual interviews and also by secondary data. The study focused on two EU approved Fish Processing Plants of Sylhet region through which fish and fishery products (mainly white fishes) are being processed for export. The findings of this study reveals that there are lot of opportunities to establish Fish Processing Plants such as availability of raw materials, low cost land, transportation facilities, suitable environment and availability of fish species in Sylhet region according to buyer’s demand. About 110 indigenous fish species were found in this region which almost half of the total number of fish species in Bangladesh. A large number of people of Sylhet region live in abroad. So, the main markets of processed fish are UK, USA and Middle East. Beside this potentiality and opportunity to enhance the export through these Fish Processing Plants the study also reveals that fish processors are facing lot of problems such as seasonality of fish species, lack of skilled personnel, high operational cost, weak infrastructure and storage facilities, international market competition, government policy, standardization, proper advertisement, low salary of workers, incentive problems with other exportable products, high interest of bank loan etc. These problems hampered the production of processed fishes of these Fish Processing Plants and also discouraged the plant owners to export